Matthew 1–13: The Gospel of Matthew, vol 1 - Wilson, Walter T. (Eerdmans Critical Commentary, 2022)
Intro -- Title Page -- Copyright -- Contents -- List of Abbreviations -- Introduction -- Section One: Matthew 1:1-5:2 -- Unit One (1:1-17) -- Unit Two, Part One (1:18-25) -- Unit Two, Part Two (2:1-12) -- Unit Two, Part Three (2:13-23) -- Unit Three, Part One-A (3:1-6) and Part One-B (3:7-12) -- Unit Three, Part One-C (3:13-17) -- Unit Three, Part Two (4:1-11) -- Transition (4:12-5:2) -- Section Two: Matthew 5:3-7:27 -- Introduction: Part One (5:3-12) -- Introduction: Part Two (5:13-16) and Part Three (5:17-20) -- Unit One, Part One (5:21-32) -- Unit One, Part Two (5:33-48) -- Unit Two (6:1-18) -- Unit Three, Part One (6:19-34) -- Unit Three, Part Two (7:1-12) -- Conclusion (7:13-29) -- Section Three: Matthew 8:1-9:38 -- Unit One (8:1-17) -- First Interlude (8:18-22) and Unit Two (8:23-9:8) -- Second Interlude (9:9-17) -- Unit Three (9:18-34) and Transition (9:35-38) -- Section Four: Matthew 10:1-42 -- Introduction (10:1-4), Unit One (10:5-15), and Unit Two (10:16-23) -- Unit Three (10:24-31) and Unit Four (10:32-42) -- Section Five: Matthew 11:1-12:50 -- Unit One (11:1-19) -- Unit Two (11:20-30) -- Unit Three (12:1-14) and Unit Four (12:15-21) -- Unit Five (12:22-37) -- Unit Six (12:38-45) and Transition (12:46-50) -- Section Six: Matthew 13:1-58 -- Unit One (13:1-23) -- Unit Two (13:24-43) -- Unit Three (13:44-52) and Coda (13:53-58) -- Bibliography.